Informed Consent in Midwifery: Bridging Legal Requirements and Patient Communication - Ayudiah, Febra; Putri, Yesi; Sulastri, Mepi (Utan Kayu Publishing, 2024)
This study investigates the implementation of informed consent within the realm of independent midwifery, with a specific focus on the communication processes and legal obligations encountered in Midwife Nela’s practice. Despite the pivotal role of informed consent in safeguarding patient rights and ensuring ethical medical practice, a significant challenge persists due to the inadequate patient awareness regarding their rights as stipulated under the 1945 Constitution. This issue often results in patients entrusting midwives without a comprehensive understanding of potential risks. Employing a normative juridical approach, this research synthesizes both primary and secondary data to explore how informed consent is executed and the attendant challenges. The findings reveal that Midwife Nela’s practice is characterized by a personalized approach to patient communication and clarity in the conveyance of information, which distinctly supports the establishment of legal and therapeutic relationships between midwives and patients. The study further discusses the implications of these findings for the enhancement of informed consent practices in independent midwifery across Indonesia. It underscores the necessity for midwives to not only fulfill legal standards but also engage in effective communication, thereby facilitating patient autonomy and informed decision-making. Recommendations are provided for improving health policies and practices, which aim to strengthen the legal protections for both patients and healthcare providers in the midwifery sector.